Microplastics in mainstem Mississippi River fishes - Gad, Ahmed K.; Toner, Kerrin; Benfield, Mark C.; Midway, Stephen R. (Frontiers in Environmental Science, 2023)
Microplastics are ubiquitous in earth’s ecosystems and many efforts have begun to understand their distributions. Large rivers, like the Mississippi River, provide a unique system in which to look at large-scale patterns of microplastic distribution. In this study, we sampled four species of widely distributed fish species from five sites along the mainstem Mississippi River, from Minnesota to Louisiana, USA. Microplastics were found in all fish species and at all sites; however, microplastics increased in occurrence in the Lower Mississippi River. Fragments were the most common morphologies and polypropylene was the most common polymer detected. We also examined the hypothesis that microplastic loads in fishes increased downstream but found support for this hypothesis only when examining Largemouth Bass; Flathead Catfish, Shortnose Gar, and Bluegill were all found to have similar microplastic loads along the mainstem Mississippi River. It is clear that microplastics are heterogeneously distributed throughout ecosystems, and further understanding of microplastic distributional patterns and varying species burdens is needed to fully understand the threat that microplastics present.